Renewable Energy Utilization and Environmental Pollution Control in the New City Area Mamminasata Metropolitan, Indonesia - Surya, Batara; Taibe, Patmawaty; Sariman, Syahrul; Hernita, Hernita; Salim, Agus; Nasrullah, Nasrullah; Hazairin Zubair, Arie Gunawan (International Journal of Energy Economics and Policy, 2023)
The dynamics of the development of the Mamminasata Metropolitan new city area has an impact on environmental quality degradation. The increase in development activities causes land use conversion and contributes to an increase in energy demand. This study aims to analyze: the allocation of work space utilization as a determinant of environmental quality degradation in the Mamminasata new city area, the effect of controlling space utilization, renewable energy utilization, and transportation management on improving the environmental quality of the Mamminasata new city area; and formulate a model for the use of renewable energy and the sustainable development of the Mamminasata Metropolitan new city area. This study uses an explanatory suqiental approach. Data were obtained through observation, surveys, in-depth interviews, and documentation. The results of the study indicate that the allocation of land for the development needs of socio-economic activities in the new city area has an impact on increasing the burden of pollution on soil, water, and air as well as the complexity of the transportation system in the direction of decreasing environmental quality. Control of space utilization, renewable energy utilization, and transportation management simultaneously have an effect on improving the environmental quality of the Mamminasata new city area with a coefficient of determination of 94.84%. This study recommends the use of renewable energy in supporting socio-economic activities towards the sustainability of the Mamminasata Metropolitan new city area development.